Fractional-order hybrid control of robots manipulators - Tenreiro Machado, J. A. (1998)
In this paper it is studied the implementation of fractional-order algorithms in the position/force hybrid control of robotic manipulators. The system robustness and performances are analysed, in terms of time responses, and compared with other control approaches. Moreover, it is also investigated the effect of nonlinear phenomena at the robot joints such as nonlinear friction, dynamic backlash and flexibility.